Invito a Vico - Fulvio TESSITORE (I Quaderni del LAB, 2018)
This book contains eight essays on Vico written by Pietro Piovani between 1968 and 1976. It is the only collection of writings on Vico designed by the author, for a publication in Spanish. Although the single essays had the widest circulation and impact since their writing, this is the first time that the collection as it was conceived by the author it is published in Italian.